2020
DOI: 10.3390/microorganisms8101626
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis on Antimicrobial Resistance Trends and Prevalence of β-lactamases in Escherichia coli and ESKAPE Pathogens Isolated from Arabian Patients during 2000–2020

Abstract: The production of diverse and extended spectrum β-lactamases among Escherichia coli and ESKAPE pathogens is a growing threat to clinicians and public health. We aim to provide a comprehensive analysis of evolving trends of antimicrobial resistance and β-lactamases among E. coli and ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acine to bacter baumannii, Pseudomonas aeruginosa, and Enterobacter species) in the Arabian region. A systematic review was conducted in Medline P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 113 publications
0
11
1
Order By: Relevance
“…[ 21 22 ] In addition, previous studies from Oman have indicated high level increase in resistance to piperacillin-tazobactam in the past 20 years, while relatively lower resistance was reported against aminoglycosides (gentamicin and amikacin) and quinolones. [ 23 ] However, resistance rate of A. baumannii to aminoglycosides, quinolones, and trimethoprim-sulfamethoxazole was also significantly high in our study. This is congruent with previous studies conducted worldwide.…”
Section: Discussioncontrasting
confidence: 58%
“…[ 21 22 ] In addition, previous studies from Oman have indicated high level increase in resistance to piperacillin-tazobactam in the past 20 years, while relatively lower resistance was reported against aminoglycosides (gentamicin and amikacin) and quinolones. [ 23 ] However, resistance rate of A. baumannii to aminoglycosides, quinolones, and trimethoprim-sulfamethoxazole was also significantly high in our study. This is congruent with previous studies conducted worldwide.…”
Section: Discussioncontrasting
confidence: 58%
“…In contrast, many recent studies have shown an increase in AMR, particularly for Gram-negative bacteria. 22 , 23 Since this work aimed to further explore the possible impact of interventions on controlling the spread of MDR bacteria at our setting, as an update of a previous study, 13 the continuing decrease over time in the relative prevalence of MDR bacteria suggests that greater attention to the AMR issue has a positive impact. Consistently, the antibiotic consumption at our institute was lower than that at other hospitals in the Calabria Region, especially for ceftriaxone, meropenem, and piperacillin/tazobactam, 12 even if the effect of reduction in antimicrobial consumption on AMR has been demonstrated to be inconsistent for all drugs and limited in time.…”
Section: Discussionmentioning
confidence: 98%
“…The acronym ESKAPE refers precisely to the "escape" of these bacteria from the action of antibiotics [4]. Infections with these bacteria are especially common in hospitalized and/or immunocompromised patients and in those with intestinal flora dysbiosis [7,8] and pose a serious threat to the life and health of these patients.…”
Section: The Eskape Group Of Bacteria As a Great Medical Challengementioning
confidence: 99%